Evaluation of the Tolerance of Four Pistachio Rootstocks to Salinity Stress Based on Morphological, Physiological and Biochemical Parameters - Samanah Hakimnejad; Hamid reza Karimi; Seyyed Rasoul Sahhafi; Majid Esmaeilizadeh(new) (Journal of Nuts, 2022)
In order to evaluation of  the tolerance of four pistachio rootstocks to salinity stress an experiment was performed as factorial in framework completely randomized design with four replications. Factors included rootstocks (‘Badami-e- Riz-e-Zarand’, ‘Ghazvini’, ‘Akbari’ and UCB-1) in four levels and salinity (0, 75 and 150 mM) in three levels.  Results showed that rootstocks had different responses to salinity. The highest specific leaf weight and chlorophyll fluorescence parameter (Fv/Fm) were observed in ‘Badami-e- Riz-e-Zarand’ and ‘Ghazvini’ rootstocks. Also, potassium and calcium concentration of shoot in ‘Badami-e- Riz-e-Zarand’, ‘Ghazvini’ and, ‘Akbari’ rootstocks were higher compared to UCB-1. The UCB-1 rootstock had higher leaf area, relative water content (RWC) and chlorophyll-a content than the other rootstocks. The results of cluster analysis showed that salinity changed the position of the ‘Akbari’ and UCB-1 rootstocks in cluster whereas the position of ‘Badami-e- Riz-e-Zarand’ and ‘Ghazvini’ rootstocks unchanged in cluster.